The Treaty on the ground : where we are headed, and why it matters (Massey University Press, 2017)
It's 175 years since the signing of the Treaty of Waitangi. At times they've been years of conflict and bitterness, but there have also been remarkable gains, and positive changes that have made New Zealand a distinct nation. This book takes stock of where we've been, where we are headed, and why it matters. Written by some of the country's leading scholars and experts in the field, it ranges from the impact of the Treaty on everything from resource management to school governance. Its focus is the application of the Treaty from the viewpoint of practitioners--the people who are walking and talking it in their jobs, communities or everyday lives--and it vividly tracks the ups and downs of bringing the spirit and principles of the Treaty to fruition.